Enhancing the Electrocatalytic Activity of Fe Phthalocyanines for the Oxygen Reduction Reaction by the Presence of Axial Ligands: Pyridine-Functionalized Single-Walled Carbon Nanotubes - Zagal-Moya, J; Zagal-Moya, J; Silva-Rojas, J; Silva-Rojas, J; Ponce-Hormazabal, I; Silva-Gonzalez, N; Silva-Gonzalez, N; Oyarzun-Medina, M; Oyarzun-Medina, M (Elsevier Ltd, 2021)
We have examined the electrocatalytic activity of iron phthalocyanine (FePc) and perchlorinated iron phthalocyanine 16(Cl)FePc for the oxygen reduction reaction (ORR) in alkaline medium with the two molecules either adsorbed on the external surface of single-wall carbon nanotubes (SWCNT) or covalently anchored via an axial pyridine ligand on pyridine-functionalized single-wall carbon nanotubes (py-SWCNT). Regardless of the particular phthalocyanine type, the ORR activity is higher when the substrate is py-SWCNT rather than SWCNT. The Tafel slopes for ORR are very similar for the two Fe macrocyclic complexes attached to SWCNTs in the two different configurations, suggesting a common rate-determining step for the ORR for all four catalysts. It is also observed that, for both the SWCNT and py-SWCNT supports, the ORR activity is higher for 16(Cl)FePc than for FePc. This is attributed to the electron-withdrawing effect of the peripheral and non-peripheral chlorine atoms in the macrocyclic ligand. While FeN4 macrocycles are known to be located on the strong binding side of a volcano correlation including several MN4 species, the chlorine substituents decrease the binding energy of O2 on the central Fe cation, thereby moving up the macrocycle catalyst towards the apex of the volcano correlation. Both the carbon surface and macrocyclic ligand effects were optimized with 16(Cl)FePc attached to py-SWCNT, which is more active than both FePc on SWCNT and FePc on py-SWCNT. Here we show that both the axial ligand and the electron withdrawing groups (-Cl) have a combined collaborative effect in increasing the catalytic activity for ORR of Fe-phthalocyanines confined on the external walls of single-wall carbon nanotubes. © 2021